Anarcos, curdas y meretrices: El “tano” en el primer teatro de Armando Discépolo - De Aldama Ordóñez, Celia (Verbum – Analecta Neolatina, 2019)
Why rescue from oblivion the two works La fragua (1912) and El vértigo (1919) by the well-known Argentine playwright Armando Discépolo? The answer has to do with the point of view that in them, the tano, a new kind of personality, occupies a central stage in the dramatic conflicts that unfold. The perspective adopted in this paper will highlight: 1. the restorative function implied in the ideological structure that governs the representation of these foreign characters; 2. their dialogue with the stereotypes of the Italian bomber/drunkard and the gringa prostituta, terms used since the end of the century by the ruling elites to criminalize the foreigner; and 3. the high testimonial value of both works whose plots are deeply anchored in the immediate socio-political conjuncture.